PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN LAGU TERHADAP KEAKTIFAN SISWA DAN HASIL BELAJAR SISWA DI KELAS 3 SD KRISTEN SAINT JOHN BEKASI - Donald Samuel Slamet Santosa; Mikhael Christupar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2021)
This research departs from the problem of the poor quality of online learning carried out by teachers since the Covid-19 pandemic. This causes low students activeness and learning outcomes. The purpose of this study was to increase students’ activeness and learning outcomes in the classroom through the media of songs. Furthermore, this research was to increase students’ learning outcomes. The research method used was Classroom Action Research (CAR) with the model used by Kemmis & Tagart. The object of the research was students of class 3B with a total of 21 students at Saint John Christian Elementary School in Indonesian Language subject. Data collection using an assessment rubric to measure student activity and a test to measure student learning outcomes. Data were analyzed descriptively. The results obtained on student activeness were that students who were categorized as very active and active reached 90% of students in the second cycle. On student learning outcomes, the results obtained are students who get complete results on student learning outcomes in the pre-cycle are 50% of students, in cycle 1 there are 89% of students and in cycle 2 are 91%. From these results, it has exceeded the target of the target, which should be 90% of students complete their learning outcomes. The conclusion is song learning media is able to increase students’ activeness and learning outcomes. This research is suggested for the teachers to use song learning media to increase student activeness and student learning outcomes.